2013
DOI: 10.1155/2013/657424
|View full text |Cite
|
Sign up to set email alerts
|

Allergen-Specific IgG Antibodies Purified from Mite-Allergic Patients Sera Block the IgE Recognition ofDermatophagoides pteronyssinusAntigens: AnIn VitroStudy

Abstract: One of the purposes of specific immunotherapy (SIT) is to modulate humoral immune response against allergens with significant increases in allergen-specific IgG levels, commonly associated with blocking activity. The present study investigated in vitro blocking activity of allergen-specific IgG antibodies on IgE reactivity to Dermatophagoides pteronyssinus (Dpt) in sera from atopic patients. Dpt-specific IgG antibodies were purified by ammonium sulfate precipitation followed by protein-G affinity chromatograph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 39 publications
0
14
0
3
Order By: Relevance
“…In humans with AD, ASIT has been associated with the development of allergen‐specific IgG levels, especially IgG1 and IgG4. In some studies, these antibodies (especially IgG4) have been demonstrated to bind to relevant allergen epitopes, thus ‘blocking’ the binding of allergen‐specific IgE . Whether canine IgG subisotypes can mediate a similar blocking effect remains to be determined.…”
Section: Update On the Role Of Antibodies In Atopic Dermatitismentioning
confidence: 99%
“…In humans with AD, ASIT has been associated with the development of allergen‐specific IgG levels, especially IgG1 and IgG4. In some studies, these antibodies (especially IgG4) have been demonstrated to bind to relevant allergen epitopes, thus ‘blocking’ the binding of allergen‐specific IgE . Whether canine IgG subisotypes can mediate a similar blocking effect remains to be determined.…”
Section: Update On the Role Of Antibodies In Atopic Dermatitismentioning
confidence: 99%
“…in schistosome‐endemic areas, the inverse association observed between infection with the parasite and allergies could be due to the anti‐schistosome CCD IgG in some way blocking the activity of allergen‐specific IgE, thereby preventing allergic reactivity. In this context, allergen‐specific immunotherapy is commonly found to induce production of anti‐allergen IgG antibodies, particularly of the IgG4 subclass, and these have been shown to block in vitro reactions mediated by allergen‐specific IgE . IgG antibodies induced by helminth infection may have a similar effect.…”
Section: Discussionmentioning
confidence: 99%
“…Siman et al 41 identifi caron proteínas IgG que pueden bloquear la actividad de la IgE específi ca a péptidos de Der p que se produjeron después de la inmunoterapia por pacientes con rinitis. Velázquez et al 42 compararon en tres grupos (con o sin ITSC y control) los niveles de IL-2, IL-4, IL-5, IL-6, IL-12, IgG4 e interferón gamma.…”
Section: Estudios Experimentales De It En América Latinaunclassified